California real estate license preparation - Pivar, William H. (Thomson/South-Western, 2008)
Thousands of real estate professionals like you have successfully prepared for and passed their California Real Estate license exam using this classic prep guide. The text provides a complete background in California real estate principles and reflects the most recent changes in California real estate licensure requirements while delivering more than 1,700 quality real estate exam questions and three 150-question review exams for complete exam preparation. You'll also appreciate how the authors provide helpful instruction and hands-on experience in examination techniques